Improved space vector modulation with reduced switching vectors for multi-phase matrix converter [electronic resource] - S. K. Moin Ahammed, 1983-, author 602191; Zainal Salam, supervisor 354781; Fakulti Kejuruteraan Elektrik 540663 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2016)
Thesis (Doktor Falsafah (Kejuruteraan Elektrik))